Conversion Of Oil Palm Empty Fruit Brunch (Opefb) Into Hydrochar Via Hydrothermal Carbonization And Study On The Suitability For Soil Ammendment - Raman, Logan Raj (Universiti Sains Malaysia, 2022)
Recently, there is a high interest in the synthesis of hydrochar from agricultural waste/residue and therefore, this approach does not only eliminate the abundant agricultural waste, but also converts the wastes into valuable product. Therefore, this paper highlights on the synthesis of hydrochar from oil palm empty fruit brunch (OPEFB), via hydrothermal carbonization (HTC) reaction. Hydrothermal carbonization is found to be an attractive process, due to its ability to transform wet biomass into hydrochar without pre-drying. Meanwhile, hydrochar, has received attention because of its ability to be applied for many applications such as precursors of adsorbent for in wastewater treatment, solid fuels and also for soil amendment. In this paper, the HTC reaction was conducted at various temperature (180 and 220 ◦C) and residence times (0.5 hr, 1hr, 2 hr) and along with this, the effect of temperature and reaction time on yield of hydrochar was also investigated. From the investigation, it is found that reaction time and temperature is directly proportional to the hydrochar yields as at highest temperature and reaction time the yield produced was 65.7%. When the temperature reduced, the yield was reduced to 48.22%, while as the reaction time reduce to 1 hr the yield was reduced to 54.51%. However, as the effect of both parameters evaluated, the finding reveals that process was most influenced by temperature compared to reaction time. Then this study, also includes the physicochemical properties study of hydrochar, which were analysed by using various analysis namely BET, SEM, FTIR and TGA -DTA. The analysis of BET and SEM, reveals that surface morphology was improved such that in BET study the surface area of hydrochar improved from 1.26